2013
DOI: 10.1149/2.019403jes
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Microstructure on the Sensing Behavior of NOxExhaust Gas Sensors

Abstract: The role of porosity on impedancemetric NO x sensing was investigated for sensors composed of a porous Y-stabilized ZrO 2 (YSZ) electrolyte and Au wire electrodes. NO x sensors were fabricated at firing temperatures of 950 • C, 1000 • C, and 1050 • C to establish different porous microstructures. Porosity calculations were determined from scanning electron microscopy images of the porous electrolytes using a three-dimensional statistical method. The mean porosity of sensors fired at 950 • C was 50.2%, and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 14 publications
2
15
0
Order By: Relevance
“…This trend was observed for each of the various gas compositions measured and likely relates to the electrolyte microstructure. Other studies have reported that the activation energy in porous electrolyte NO x sensors tends to increase with increasing electrolyte porosity [3]. Table 1 shows the porosity of the electrolytes increased as the FSZ content in the sensor electrolyte increased.…”
Section: Rate Limiting Mechanisms and Activation Energiesmentioning
confidence: 87%
See 2 more Smart Citations
“…This trend was observed for each of the various gas compositions measured and likely relates to the electrolyte microstructure. Other studies have reported that the activation energy in porous electrolyte NO x sensors tends to increase with increasing electrolyte porosity [3]. Table 1 shows the porosity of the electrolytes increased as the FSZ content in the sensor electrolyte increased.…”
Section: Rate Limiting Mechanisms and Activation Energiesmentioning
confidence: 87%
“…Studies have found the porosity of the electrolyte effects gas transport to the triple phase boundary (TPB) [3,7]. The TPB is the location where the electrolyte, electrode, and gas phase are in contact.…”
Section: Morphology and Microstructurementioning
confidence: 99%
See 1 more Smart Citation
“…In a recent critical review of the chemoresistive gas sensors, Sadek et al [13] believe that dependence of sensor response on operating temperature originates from varying adsorption and desorption kinetics for oxygen ions on the oxide surfaces. The investigated material in this publication has a similar structure to the so called lambda sensor based on YZrOx, for which oxygen ion diffusion through vacancies in the material and detection of the potential gradient over the material, constitutes the detection mechanism [14][15][16]. Therefore, also oxygen diffusion through vacancies in the Au/InZrOx may form at least part of the sensor detection mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…Zirconia is one of the most commonly used O2 and NOx sensing material [14][15][16], whereas indium oxide is a semiconductor oxide that is recently being used as active material in exhaust gas sensors [17][18][19].…”
Section: Introductionmentioning
confidence: 99%